Implementasi Kebijakan Penataan Ruang Terbuka Hijau Sebagai Upaya Mewujudkan Tata Kelola Kawasan Kota Berbasis Lingkungan (Eco City) Yang Berkelanjutan - Sarah Riska Arifiah; Suhartoyo Suhartoyo (Administrative Law and Governance Journal, 2022)
Abstract: Sustainable development is very important and necessary in a country, the goal is to be able to meet the needs of human life today without ignoring the needs of human life in the future. Likewise with cities that require sustainable regional management, especially in relation to environmental-based city governance (eco city). Green open space is one form of the eco city component. Semarang is the capital city in Central Java which has regulatory instruments regarding green open spaces, namely Semarang City Regional Regulation No. 7 of 2010 concerning the Arrangement of Green Open Space. The problems of this research are, how is the policy of the Semarang City Government in structuring green open spaces in order to create a sustainable city, and how is the implementation of green open space management policies in order to create a sustainable city by the Semarang City Government. From research and research analysis, the formulation of conclusions obtained is regarding the policy of the Semarang City Government in carrying out wide-spread activities on the availability of green open space in the city of Semarang. As well as green open space programs implemented in the city of Semarang to maintain the sustainability of green open space. Based on the results of the research analysis, the recommendations of the researchers include the following, the participation that needs to be increased by the Semarang City Government with stakeholders, the community and NGOs in the context of realizing the wide distribution of green open space in the city of Semarang, and activities for the wide dissemination of green open space which should be implemented immediately, so as not to accumulate in several sub-districts in the Semarang City area Keywords :  Sustainable Development,  Environmental-Based City Governance, Green Open Space Abstrak: Pembangunan berkelanjutan sangat penting dan diperlukan pada suatu negara, tujuannya agar dapat memenuhi keperluan hidup manusia pada masa kini dengan tanpa mengabaikan keperluan hidup manusia pada masa mendatang. Begitu juga dengan kota yang memerlukan tata kelola kawasan yang berkelanjutan terutama kaitannya dengan tata kelola kota berbasis lingkungan (eco city). Ruang terbuka hijau (RTH) merupakan salah satu bentuk dari komponen eco city. Kota Semarang merupakan ibu kota di Jawa Tengah yang memiliki instrumen pengaturan mengenai ruang terbuka hijau, yaitu Perda Kota Semarang No. 7 Tahun 2010 tentang Penataan Ruang Terbuka Hijau. Permasalahan dari penelitian ini yaitu, bagaimana kebijakan Pemerintah Kota Semarang dalam melakukan penataan ruang terbuka hijau guna mewujudkan kota berkelanjutan, serta bagaimana implementasi kebijakan penataan ruang terbuka hijau guna mewujudkan kota berkelanjutan oleh Pemerintah Kota Semarang.Dari penelitian dan analisis penelitian, rumusan kesimpulan yang diperoleh adalah mengenai kebijakan Pemkot Semarang dalam melakukan kegiatan sebaran luas terhadap ketersediaan RTH di Kota Semarang. Serta program-program RTH yang dilaksanakan di Kota Semarang untuk menjaga keberlangsungan RTH. Berdasarkan hasil analisis penelitian, rekomendasi peneliti meliputi hal-hal, partisipasi yang perlu ditingkatkan lagi oleh Pemkot Semarang dengan para stakeholders, masyarakat dan LSM dalam rangka realisasi sebaran luas RTH di Kota Semarang; serta kegiatan penyebaran luas RTH yang hendaknya segera dilaksanakan, agar tidak menumpuk di beberapa kecamatan di wilayah Kota Semarang Kata kunci : Pembangunan Berkelanjutan, Tata Kelola Kota Berbasis Lingkungan, Ruang Terbuka Hijau